Graining the grains; a link to equality - Appiah, James Ekow (2017)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the Degree of Master of Fine Art (Painting and Sculpture).